A Comparison of Modifications Induced by Li3+ and Ag14+ Ion Beam in Spectroscopic Properties of Bismuth Alumino-Borosilicate Glass Thin Films. (19th November 2012) - Kaur, Ravneet; Singh, Surinder; Pandey, Om Prakash
Abstract : Ion irradiation effects on the glass network and structural units have been studied by irradiating borosilicate glass thin film samples with 50 MeV Li 3+ and 180 MeV Ag 14+ swift heavy ions (SHI) at different fluence rates ranging from 10 12 ions/cm 2 to 10 14 ions/cm 2 . Glass of the composition (65- x ) Bi2 O3 -10Al2 O3 -(65- y ) B2 O3 -25SiO2 ( x = 45, 40; y = 20, 25) has been prepared by melt quench technique. To study the effects of ionizing radiation, the glass thin films have been prepared from these glasses and characterized using XRD, FTIR, and UV-Vis spectroscopic techniques. IR spectra are used to study the structural arrangements in the glass before and after irradiation. The values of optical band gap, Urbach energy, and refractive index have been calculated from the UV-Vis measurements. The variation in optical parameters with increasing Bi2 O3 content has been analyzed and discussed in terms of changes occurring in the glass network. A comparative study of the influence of Li 3+ ion beam on structural and optical properties of the either glass system with Ag 14+ ion is done. The results have been explained in the light of the interaction that SHI undergo on entering the material.